UI dan UX Aplikasi Peminjaman Kendaraan Dinas Operasional pada Sudin Pusip JT - Eddiansyah Ragil Saputra; Susy Rosyida (Universitas Wahid Hasyim, 2024)
The East Jakarta Library and Archives Sub-agency has operational official vehicles that can be used by employees in carrying out tasks outside the office. The process of borrowing operational official vehicles is done manually, by way of employees coming to the general section to apply for a vehicle loan and the general section to check the vehicle. Applications for loaning operational service vehicles are often made from other employees, due to a lack of information regarding vehicle loan data and no information regarding vehicle loan reports. With this problem in mind, a User Interface (UI) and User Experience (UX) design was carried out using the design thinking research method aimed at the needs of prospective users, and using the User Persona and figma tools to focus on target users who will use the system display. The operational official vehicle loan information system can make it easier for employees to borrow vehicles and avoid borrowing carried out simultaneously.